THE ISLAMIC MOVEMENT OF UZBEKISTAN: LINES TO COMPLETE THE PORTRAIT - RUZALIEV, Odil (CENTRAL ASIA AND THE CAUCASUS, 2004)
In 2000, the Islamic Movement of Uzbekistan, or the IMU, became the first terrorist group in the post-Soviet space to be included in the U.S. Department of State “List of Foreign Terrorist Organizations.” Despite its name, the IMU is com-posed of citizens of all the Central Asian states, Chinese Xinjiang province, Chechnia, and some Arab countries. The IMU’s main objective is to create an Islamic state in the Ferghana Valley and consequently in the whole of Uzbekistan. It is sup-ported by Islamic radicals around the world as well as intelligence services of some countries. The IMU also has links to Osama bin Laden’s al-Qa‘eda and fought against the Northern Alliance of Ahmad Shah Masood alongside the forces of the Taliban Movement of Afghanistan. It carried out terrorist attacks in Uzbekistan and made incursions into neighboring Kyrgyzstan. For years the international community and mainly Western states had been blind to the civil war in Afghanistan, the Taliban’s stone-age policy and enormous drug business. The world regained its sight as a result of the tragedy of 11 September 2001 in the United States that promptly shifted the attention of the international community to Afghanistan. International terrorism’s home, Afghanistan, was bombed. International terrorism’s patron, the Taliban movement, was destroyed. Terrorists lost their home and were deprived of security; their base and financial system were damaged. Though not completely rooted out, the threat of the Islamic Movement of Uzbekistan to Central Asia was greatly diminished. Its military leader is thought to have been killed during the U.S.-led war in Afghanistan and its political leader is believed to be in hiding. Fol-lowing the Operation Enduring Freedom in late 2001, the IMU renamed itself the Islamic Move-ment of Turkestan (IMT), thus openly proclaim-ing its purposes of controlling the entire Central Asian region, disregarding the five existing nation-states and their boundaries. This paper is about the Islamic Movement of Uzbekistan’s history, structure, objectives, tactics, leadership, and links to other terrorist and religious extremist groups as well as to al-Qa‘eda and bin Laden. I will explain the conditions under which the movement came into existence and flourished in a country that was atheist for decades, and external factors that nourished its existence. In conclusion I will cover the implications the 2001 war in Afghanistan had on the IMU and its future impact on the security of Central Asia.